Investigating Development of Feminist Pedagogy in Universities: Learning from Gender Studies, Universitas Indonesia - Mia Siscawati (Yayasan Jurnal Perempuan, 2016)
This paper explores the trajectory of feminist pedagogy development in higher education institution in Indonesia, especially in Gender Studies Graduate Program at Universitas Indonesia that manages the master degree program on gender studies since 1990. The development of feminist pedagogy in this higher education institutionis influenced by the commitment of the top leader(s), the support of lecturers representing multidisciplinary background, collaborations with other universities, as well as a close synergy between academics and activists. In presenting and discussing the development of feminist pedagogy in Gender Studies Graduate Program of UI since its inception to the present time, this paper uses literature reviews, critical reflection of students, and other personal reflective notes as main ingredients.